(untitled) (Balthazar, 2023)
This study looks into H. P. Lovecraft’s masterful craft of cosmic horror, examining his adept fusion of Christian cosmological elements with subversion and mockery, while concurrently forging a unique cosmic framework. Lovecraft subtly weaves Christian themes into his mythos, introducing his eldritch terrors, deities reminiscent of Christian demonology. These entities, residing in abyssal depths, bear distinctly demonic attributes, highlighting the profound influence of Christian cosmology. The enigmatic entity Dagon, rooted in biblical mythology, is a focal point. Its appearances correlate with catastrophic consequences and the underworld, subverting Christian narratives and invoking a sense of dread through an alternative lens. Lovecraft strategically manipulates Christian celebrations, such as May-Eve and All-Hallows, challenging their significance and intensifying readers’ religious discomfort. Lovecraft’s cosmic framework is non-anthropocentric, portraying an indifferent universe inhabited by ancient cosmic entities beyond human comprehension. However, he alludes to an impending chaos, drawing subtle parallels with the biblical Apocalypse. Lovecraft’s narratives interweave Christian cosmology, subversion, and mockery, challenging religious frameworks while invoking terror and fascination, providing a rich tapestry for scholarly analysis in cosmic horror literature.